TRADISI MALAM SATU MUHARAM DI PONDOK PESANTREN TAHFIDZUL QURAN AL HIKMAH PURWOASRI KEDIRI - Husna, Nailyl Fida (Living Islam: Journal of Islamic Discourses, 2022)
AbstractThis article briefly describes one of the traditions of welcoming the arrival of the first night of Muharram. Indonesia is known for its diversity of traditions, customs and cultures, most of which were born before the arrival of Islam. This raises a big question mark about the validity of the tradition. Therefore, the ulama' are looking for a middle way between the two, which can be done but does not conflict with the religious law. One example is the tradition at the Tahfidzul Quran Al Hikmah Islamic Boarding School which has a tradition of reading the verse of the chair every night one Muharram. As for the procedure, it begins with prayer at the beginning and end of the year followed by prayer in congregation, tawassul, reading the verse of the chair 360 times (starting with basmalah in each verse and reading it in one seat) and ending with a prayer together. The method used in this paper is a descriptive qualitative approach with the type of field research and the living Quran theory approach. The results of the application of the theory show that the annual tradition at the Tahfidzul Quran Al Hikmah Islamic Boarding School is a practice obtained by KH. Abdun Nasir from his teacher Sheikh Maliki which is written in the book Kunuzu an-Najah Wa as-surur. Reading the verse of the chair is believed to bring many benefits including; protector from all dangers such as supernatural beings, clears the mind, amulets, tattoos and increases self-confidence etcKeywords: Muharram, Islamic bording school, ayat kursi Abstrak  Artikel ini menjelaskan secara singkat salah satu tradisi penyambutan datangnya malam satu Muharam. Indonesia dikenal dengan keanekaragaman tradisi, adat dan budayanya, sebagian besar tradisinya terlahir sebelum datangnya Islam. Hal ini, menimbulkan tanda tanya besar tentang keabsahan tradisi tersebut. Oleh karena itu, para ulama’ mencari jalan tengah antara keduanya, dapat dikerjakan namun tidak bertentangan dengan syariat agama.para ulama’ menegaskan, diperbolehkan melakukan semua tradisi asalkan tidak menyekutukan Allah. Salah satu contohnya tradisi di Pondok Pesantren Tahfidzul Quran Al Hikmah yang mempunyai tradisi membaca ayat kursi setiap malam satu Muharam. Adapun tata caranya, diawali dengan doa awal dan akhir tahun dilanjutkan sholat berjamaah, tawassul, membaca ayat kursi sebanyak 360 kali (diawali dengan basmalah di setiap ayatnya dan dibaca dalam satu dudukan) dan diakhiri dengan doa bersama. Metode yang digunakan dalam tulisan ini ialah pendekatan kualitatif deskriptif dengan jenis penelitian lapangan (field research) dan pendekatan teori living Quran. Adapun hasil penerapan teori tersebut menunjukkan, tradisi tahunan di Pondok Pesantren Tahfidzul Quran Al Hikmah merupakan amalan yang diperoleh KH. Abdun Nashir dari gurunya Syeikh Maliki yang tertulis dalam kitab Kunuzu an-Najah Wa as-surur. Membaca ayat kursi diyakini membawa banyak manfaaat diantaranya; pelindung dari segala mara bahaya seperti makhluk-makhluk ghaib, menjernihkan pikiran, jimat, rajah dan meningkatkan percaya diri dll. Kata Kunci: Muharam, pondok pesantren, ayat kursi